2013
DOI: 10.1007/s00280-013-2258-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic determinants associated with sunitinib-induced toxicity and ethnic difference in Korean metastatic renal cell carcinoma patients

Abstract: Among 12 genetic polymorphisms, polymorphism in the ABCG2 421C>A gene may be mostly associated with the risk of sunitinib-related toxicity in mRCC patients. Considering the high frequency of 421C>A SNP in Asian, this may be related to differential toxicities among ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 33 publications
3
46
2
Order By: Relevance
“…The association of sunitinib-induced toxicities with pharmacogenetic determinants was studied by Kim et al in 65 Korean mRCC patients [49]. Compared to C-allele carriers, patients with the AA variant genotype of the drug transporter ABCG2 rs2231142 had an increased risk for grade 3 or 4 thrombocytopenia, neutropenia and hand-foot syndrome [49]. As to the relation of this SNP with pharmacokinetic parameters, Mizuno et al clarified the effect of the ABCG2 rs2231142 genotype in 19 Japanese RCC patients [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…The association of sunitinib-induced toxicities with pharmacogenetic determinants was studied by Kim et al in 65 Korean mRCC patients [49]. Compared to C-allele carriers, patients with the AA variant genotype of the drug transporter ABCG2 rs2231142 had an increased risk for grade 3 or 4 thrombocytopenia, neutropenia and hand-foot syndrome [49]. As to the relation of this SNP with pharmacokinetic parameters, Mizuno et al clarified the effect of the ABCG2 rs2231142 genotype in 19 Japanese RCC patients [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Sunitinib-induced toxicities in relation to pharmacogenetic determinants were studied by Kim et al [27] in a number of 65 Korean mRCC patients. Compared to C-allele carriers, the AA genotype of rs2231142 in ABCG2 had an increased risk for grade 3 or 4 thrombocytopenia, neutropenia, and HFS [27].…”
Section: Pharmacogenetics To Predict Sunitinib Toxicitymentioning
confidence: 99%
“…Compared to C-allele carriers, the AA genotype of rs2231142 in ABCG2 had an increased risk for grade 3 or 4 thrombocytopenia, neutropenia, and HFS [27]. In addition, a case report of Takayoshi et al [28] reported a 65-year-old woman with mRCC who showed severe toxicities and was found to have the TTT haplotype on ABCB1 (rs1045642, rs1128503, rs2032582).…”
Section: Pharmacogenetics To Predict Sunitinib Toxicitymentioning
confidence: 99%
“…9,10) This genetic polymorphism has been associated with sunitinib-induced toxicities. 11) In addition, the allele frequency of ABCG2 421C>A was found to be higher in Asians than in non-Asians, such as Caucasians and African-Americans. 12) These findings suggested that the ABCG2 polymorphism may represent one of the reasons for the ethnic differences reported in sunitinib PK and toxicity.…”
mentioning
confidence: 99%